A direct procedure for monitoring the coefficient of variation using a variable sample size scheme - Yeong, W.C.; Khoo, M.B.C.; Lim, S.L.; Lee, M.H. (Marcel Dekker (now owned by Taylor & Francis), 2017)
A variable sample size (VSS) scheme directly monitoring the coefficient of variation (CV), instead of monitoring the transformed statistics, is proposed. Optimal chart parameters are computed based on two criteria: (i) minimizing the out-of-control ARL (ARL1) and (ii) minimizing the out-of-control ASS (ASS1). Then the performances are compared between these two criteria. The advantages of the proposed chart over the VSS chart based on the transformed statistics in the existing literature are: the former (i) provides an easier alternative as no transformation is involved and (ii) requires less number of observations to detect a shift when ASS1 is minimized.